Benign Metastasizing Leiomyoma: New insights into a rare disease with an obscure etiopathogenesis - Aziz Chouchane; Sassi Boughizane; Monia Nouira; Sami Remadi (BMC, 2024)
Abstract Background Benign metastasizing leiomyoma (BML) is a rare disease with an unknown etiopathogenesis that mostly affects middle-aged women with uterine leiomyoma. Many metastatic nodules outside the uterus characterize the condition. The metastases are smooth muscle lesions without malignancy. Morphologically and immunohistochemically, they resemble uterine leiomyomas, indicating a shared clonal origin. The lungs are the most prevalent site for incidental metastasis detection. BML has a relatively slow progression and good prognosis, and historically, there has been a lack of established guidelines for its treatment. Case presentation Herein, we report a case of BML in a patient with multiple metastases. Through extensive histological and immunohistochemical analyses, this complex case enabled not only the definitive diagnosis of BML, but also shed light on its complex etiopathogenesis. Conclusion This study presents novel histology evidence suggesting a potential causal relationship between metaplasia and the development of BML.